(Meth)acrylate-functionalized waxes and curable compositions made therewith
Patent Information
- Application Number
- JP2023132857
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-08-17
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2038-12-13
Smart Images

Figure 0007634614000053 
Figure 0007634614000054 
Figure 0007634614000055
Abstract
Description
[Technical field]
[0001] The present invention relates to (meth)acrylate-functionalized waxes and curable compositions, such as anaerobic adhesive compositions made therewith. [Background technology]
[0002] (Brief Description of Related Art) Anaerobic adhesive compositions are generally well known. See, for example, R.D. Rich, "Anaerobic Adhesives," Handbook of Adhesive Technology, 29, pp. 467-79, edited by A. Pizzi and KL Mittal, Marcel Dekker, Inc., New York (1994), and references cited therein. Their uses are manifold, and new applications continue to be developed.
[0003] Conventional anaerobic adhesives typically contain free radically polymerizable acrylate ester monomers along with peroxide initiator and inhibitor components. Often such anaerobic adhesive compositions also contain accelerator components to increase the speed at which the composition cures.
[0004] Desirable anaerobic cure-inducing compositions that induce and accelerate cure can include saccharin, toluidines such as N,N-diethyl-p-toluidine ("DE-pT") and N,N-dimethyl-o-toluidine ("DM-oT"), acetylphenylhydrazine ("APH"), and maleic acid and quinones such as naphthaquinone and anthraquinone. See, for example, U.S. Patent Nos. 3,218,305 (Krieble), 4,180,640 (Melody), 4,287,330 (Rich), and 4,321,349 (Rich).
[0005] Attempts have been made in the past to produce adhesives, such as anaerobic adhesives, in a non-flowable form.
[0006] Thickeners are added to adhesives to reduce their fluidity. However, because the other components of the adhesive are liquid, the overall adhesive composition remains somewhat fluid and / or tacky. And the adhesive performance usually cannot reach its full potential due to the dilution effect caused by the thickener.
[0007] For example, U.S. Patent No. 6,727,320 (Attarwala) claims an adhesive composition comprising at least one room temperature flowable polymerizable compound and a polymeric matrix selected from urea-urethanes, hydroxy or amine modified aliphatic hydrocarbons, polyester-amide based rheological additives, and combinations thereof, present in an amount sufficient to render the composition non-flowable at temperatures up to about 180° F. (82° C.). The composition is dispensable at room temperature without the application of heat.
[0008] US Patent Application Publication US2003 / 0171467 (Kneafsy) is directed to a composition comprising (i) at least one anaerobically polymerizable compound; (ii) at least one condensation product of an aldehyde and / or ketone with a polyol, the composition being in the form of a soft solid, for example in the form of a stick.
[0009] Curable adhesive tape products are known. One such example is Loctite® from Henkel Corporation, Rocky Hill, CT. It is available under the trade name 249Quicktape. This product consists of a liquid anaerobic threadlocker sandwiched between two films of non-reactive polyamide / polyurethane film. See also U.S. Patent Application Publication No. US2012 / 0114898.
[0010] Compositions, including those suitable for use in thread lock applications, are applied in a dry to contact form and then anaerobic curing occurs.
[0011] In some cases, cure mechanisms can be used to achieve a dry-to-touch shape. For example, a first cure mechanism may form a dry-to-touch form to hold the composition in place on the article, while a second (e.g., anaerobic) cure mechanism can be activated later to achieve cure, for example, in thread lock applications.
[0012] For example, European Patent No. 0 077 659 (Thompson) describes a pre-applied polymerizable fluid for sealing and locking engineering parts. The composition operates by two curing mechanisms. The first is UV light curing. An opacifier is dispersed in the fluid, rendering the fluid substantially opaque to radiation. After the fluid is applied to a part of the part, it is exposed to UV radiation, where it forms a coating, forming a surface layer that is a dry, tack-free outer layer. The fluid beneath the skin, however, is not affected by the radiation and generally remains in a liquid state. When a part with the fluid applied (such as a screw or bolt) is screwed into another part (such as a nut), the surface layer of the fluid breaks and a second polymerization (such as a free radical polymerization) is initiated, resulting in a second curing reaction. The second polymerization mechanism acts to lock the threads together. In Thompson, since only the skin is formed in the first polymerization, while the remainder of the composition remains liquid beneath the skin, there is a risk that the skin may break during handling of the coated part, causing the liquid composition to leak out.
[0013] EP 0548369 (Usami) describes a pre-applied adhesive composition for application to the threaded contact surface of a screw. The composition comprises a photocurable binder in which a secondary curable composition is dispersed. The secondary curable composition comprises a microencapsulated reactive monomer / activator / initiator.
[0014] International Patent Application WO2004 / 024841 (Haller) describes a curable composition for application to threaded articles. The composition comprises (i) a first cure mechanism component comprising (a) a (meth)acrylate functional monomer component, (b) a (meth)acrylate functional oligomer component; (c) a photoinitiator component, and (ii) a dispersion of a second cure mechanism component comprising (d) an amine component and (e) an encapsulated epoxy resin component together with (iii) a thickener component. The photoinitiator component is suitable for irradiating the composition to achieve a first cure throughout the depth of the composition applied to the threaded article, and a binder matrix is formed with the second cure mechanism components dispersed throughout the matrix.
[0015] The English abstract of Chinese patent publication CN102558490 clearly discloses a hot-melt capable prepolymer which is a urethane or polyurethane (meth)acrylate prepolymer having (meth)acryloyl end groups. The melting point of the prepolymer is 50-80°C. An anaerobic adhesive is prepared from the hot-melt capable prepolymer, a monomer containing at least one acrylate ester group or methacryloyl group, an accelerator, a stabilizer and an initiator. A liquid monomer is mixed with the prepolymer to form a gel.
[0016] US Patent No. 8,470,932 relates to a method for producing a curable wax. The method of the '932 patent includes reacting a wax having a convertible functional group with a curable compound in the presence of an organic solvent to form a curable wax, removing excess curable compound using hot water having a temperature above about 85°C, and solidifying the curable wax. In this method, the excess curable compound is removed by carrying out at least one extraction process using hot water, during which the excess curable compound is removed from the wax phase into a water phase, and then the water phase is removed.
[0017] US Patent Publication No. US2013 / 014400 describes a urethane (meth)acrylate composition that forms a coating film that is allegedly tack-free within 30 minutes. The composition includes a urethane (meth)acrylate resin, a (meth)acrylate monomer, a paraffin wax, and an ethylene-α-co-oligomer. The paraffin wax is added as an ingredient to aid in drying of the coating film, the paraffin wax stopping the evaporation of the (meth)acrylate monomer.
[0018] U.S. Patent Publication No. US2011 / 0247521 describes a compound having the structure CH3-(CH2) n A method is described for producing curable waxes, such as acrylates of hydroxyl-terminated polyethylene waxes having -CH2OH (n is 22-24). The curable waxes are formed by the esterification reaction of hydroxyl-terminated polyethylene waxes with acrylic acid. The curable waxes are for use as radiation curable inks.
[0019] US Patent Publication No. US2007 / 0120925 similarly describes curable waxes by esterifying the wax with acrylic acid. Radiation curable inks are formed by combining a curable wax with a curable monomer such as a (meth)acrylate.
[0020] International Patent Publication No. WO2016 / 130503 describes a fluorine-free fibrous treatment composition comprising an isocyanate-derived ethylenically unsaturated monomer containing oligomer. The composition comprises one or more compounds derived from a reaction mixture comprising (i) at least one isocyanate-reactive oligomer comprising 2-20 repeat units and (ii) at least one polyisocyanate, the isocyanate-reactive oligomer being made by a radical-initiated reaction of a reaction mixture comprising at least one mercaptan and at least one (meth)acrylate monomer, where the at least one (meth)acrylate monomer comprises at least one isocyanate-derived group and at least one hydrocarbon group having at least 16 carbon atoms. Such compositions are claimed to be useful for treating fibrous substrates to enhance their water repellency.
[0021] U.S. Patent Publication No. US2005 / 0075411 describes a light-stable and weather-resistant coating film comprising a powder coating composition comprising a binder comprising 30-98.5% by weight of at least one urethane (meth)acrylate having a melting point of 40-130° C., 1-20% by weight of at least one finely divided wax, and 0.5-50% by weight of at least one auxiliary and / or at least one additive, the composition being crosslinked by actinic radiation. The coating produced has a low gloss surface.
[0022] International Patent Application Publication No. WO2017 / 068196 describes an anaerobic curable composition that includes an anaerobic curable component that is a combination of a solid resin component and a solid anaerobic curable monomer. In some examples, the solid resin component includes a (meth)acrylate-functionalized polyester polyol formed from a semi-crystalline polyester polyol. Summary of the Invention [Problem to be solved by the invention]
[0023] Notwithstanding the state of the art, it would be desirable to provide alternative anaerobic curable compositions suitable for delivery in a non-flowable form, particularly those that include solid components that harden within the anaerobic curable composition. [Means for solving the problem]
[0024] The present invention relates to (meth)acrylate-functionalized waxes and curable compositions, such as anaerobic adhesive compositions made therewith.
[0025] The anaerobically curable composition includes a (meth)acrylate component, an anaerobic cure-inducing composition, and a (meth)acrylate-functionalized wax.
[0026] (Meth)acrylate functionalized waxes can be formed from a wax having one or more hydroxyl groups reacted with a compound containing at least one isocyanate group and at least one (meth)acrylate group. Under appropriate reaction conditions, the hydroxyl groups on the wax react with the isocyanate groups to form urethane linkages that leave (meth)acrylate groups available to participate in curing reactions with other components of the curable composition.
[0027] The (meth)acrylate functionalized wax can include compounds having the formula: [ka] During the ceremony, n is 0 to 3; t is 1 to 4; Z is H or Me; R is a C2-C alkyl group optionally substituted with one or more of C1-C6 alkyl, C1-C6 alkoxy, hydroxyl, acrylate, methacrylate, and oxo. 12 is an aliphatic group, 12 aliphatic groups are optionally substituted with one or more heteroatoms selected from O, N or S; R 1is optionally substituted with one or more C1-C6 alkyl groups, C1-C6 alkoxy, hydroxyl, oxo, carbonate, or heteroatoms selected from one or more O, N, or S. 10 ~C 120 Contains an aliphatic group, R 2 is a C2-C alkyl group optionally substituted with one or more C1-C6 alkyl, C1-C6 alkoxy, hydroxyl, and optionally substituted with one or more heteroatoms selected from O, N, or S; 20 Aliphatic group, C5~C 20 Aryl group, or C6-C 20 Contains an alkaryl group.
[0028] Appropriately, R is C2~C 12 For example, R can be ethyl, propyl, butyl, pentyl, hexyl, or an isomer thereof.
[0029] Preferably, R 1 is optionally substituted with one or more C1-C6 alkyl groups, C1-C6 alkoxy, hydroxyl, oxo, carbonate, or heteroatoms selected from one or more O, N, or S. 10 ~C 120 Contains alkyl groups. For example, R 1 is C 12 ~C 80 It may be an alkyl group.
[0030] R 1 is C 18 ~C 40 may be also possible.
[0031] n is 0, 1 or 2, suitably n is 0 or 1. t may be 1, 2, 3 or 4, suitably t is 1 or 2.
[0032] R 1 Suitably has the following structure: [ka] In the formula, R3 is C1~C 12 It is an alkyl.
[0033] For example, R 1 may have the following structure: [ka]
[0034] For example, R 1 may have the following structure: [ka] In the formula, o is 15 to 30.
[0035] For example, R 1 may be: [ka] In the formula, o is 15 to 25.
[0036] R 1 may have the following structure: [ka] In the formula, p is 10 to 30.
[0037] For example, R 1 may be: [ka] In the formula, p is 15 to 25.
[0038] R 2 is C2~C 12 It can be alkyl, for example, R 2 can be ethyl, propyl, butyl, pentyl, hexyl, cyclopentyl, cyclohexyl, heptyl, octyl or an isomer thereof.
[0039] R2 may be: [ka] In the formula, x is 1 to 4, and each R 4 is independently selected from C1-C6 alkyl or C1-C6 alkoxy.
[0040] R 2 may be: [ka]
[0041] R 2 may be: [ka]
[0042] The compound may be selected from the following group: [ka] [ka] [ka]
[0043] In another aspect, the present invention provides a composition comprising: (a) a (meth)acrylate component; (b) an anaerobic cure-inducing composition; and (c) An anaerobic curable composition comprising an anaerobic curable composition comprising a compound described herein.
[0044] Suitably, the anaerobic cure-inducing composition is selected from the group consisting of cumene hydroperoxide, paramenthane hydroperoxide, t-butyl hydroperoxide, t-butyl perbenzoate, benzoyl peroxide, dibenzoyl peroxide, 1,3-bis(t-butylperoxyisopropyl)benzene, diacetyl peroxide, butyl 4,4-bis(t-butylperoxy)valerate, p-chlorobenzoyl peroxide, t-butylcumyl peroxide, lauryl peroxide, urea-hydrogen peroxide, n-vinylpyrrolidone-hydrogen peroxide, bis(t-butyl and combinations thereof.
[0045] Suitably, the compound of the present invention is present in an amount of about 10% to about 60% by weight based on the total weight of the composition, for example, about 25 to about 50% by weight based on the total weight of the composition.
[0046] The cure-inducing component is typically present in an amount of from about 0.1 to about 10 wt %, such as from about 1 to about 5 wt %, for example about 5 wt %, based on the total weight of the composition.
[0047] Advantageously, the cured compositions of the present invention are substantially dry to the contact and solvent-free. [Brief description of the drawings]
[0048] [Figure 1] FIG. 1 shows a synthetic scheme for producing a (meth)acrylate-functional wax. [Diagram 2] FIG. 2 shows a bar graph illustrating performance over time on a black oxide / mild steel substrate and a zinc phosphate coated steel substrate. [Diagram 3]FIG. 3 shows the DSC thermogram of a compound of the present invention. [Figure 4] FIG. 4 shows a DSC thermogram of a prior art (meth)acrylate-functionalized urethane. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0049] <Detailed Description> As outlined above, the present invention provides a (meth)acrylate-functionalized wax represented by a compound having the formula: [ka] During the ceremony, n is 0 to 3, t is 1 to 4, and Z is H or Me; R is a C2-C alkyl group optionally substituted with one or more of C1-C6 alkyl, C1-C6 alkoxy, hydroxyl, acrylate, methacrylate, and oxo. 12 is an aliphatic group, 12 aliphatic groups are optionally substituted with one or more heteroatoms selected from O, N or S; R 1 is optionally substituted with one or more C1-C6 alkyl groups, C1-C6 alkoxy, hydroxyl, oxo, carbonate, or heteroatoms selected from one or more O, N, or S. 10 ~C 120 Contains an aliphatic group, R 2 is a C2-C alkyl group optionally substituted with one or more C1-C6 alkyl, C1-C6 alkoxy, hydroxyl, and optionally substituted with one or more heteroatoms selected from O, N, or S; 20 Aliphatic group, C5~C 20 Aryl group, or C6-C 20 Contains an alkaryl group.
[0050] Importantly, the (meth)acrylate functionalized wax is solid or non-flowable at room temperature (about 20°C to about 25°C) and becomes flowable when exposed to elevated temperatures of at least about 30°C to about 100°C, desirably about 40°C to about 90°C, such as about 80°C.
[0051] More specifically, the (meth)acrylate-functionalized wax can be formed, in one embodiment, from long-chain aliphatic compounds having two or more hydroxyl groups. These long-chain aliphatic compounds must be solid at room temperature and become fluid when exposed to high temperature conditions of about 30° C. to about 100° C., desirably about 40° C. to about 90° C., for example about 85° C.
[0052] Typically, the (meth)acrylate functionalized wax should return to a non-flowable or solid state in less than about 60 minutes and remain curable for about 1 to about 5 months.
[0053] For example, (meth)acrylate functionalized waxes can be produced from solid or high viscosity (e.g., greater than 3 cps at 149° C. (ASTM D-3236)) hydroxyl-containing compounds such as fatty alcohols (or fatty acids that are reduced to form the corresponding straight chain alcohols (e.g., lauric (C12), myristic (C14), palmitic (C16) and stearic (C18))) or hydroxyl-containing steroids (such as cholesterol), hydroxyl-containing terpenes, and hydroxyl-containing bicyclic or tricyclic (fused, bridged or spiro) ring compounds.
[0054] Suitable examples of hydroxyl-terminated polyethylene waxes that can be functionalized with (meth)acrylate groups include those having the structure HO(CH2) n Included are compounds having the formula CH2OH, where the chain length n can be 1 or greater, but the average chain length ranges from about 16 to about 50, such as from about 20 to about 30.
[0055] For example, a hydroxyl-terminated compound that may be functionalized with a (meth)acrylate group may have the formula: [ka] In the formula, each R 3 are C1 to C 12 is an aliphatic group, and each s is an integer ranging from about 5 to about 30.
[0056] Suitably each s is in the range 5 to 15, for example 6 or 7 or 8 or 9 or 10 or 11 or 12 or 13 or 14.
[0057] Hydroxyl-terminated waxes suitable for forming the (meth)acrylate-functionalized wax in accordance with the present invention may have the formula: [ka] In the formula, each R 3 are C1 to C 12 It is an alkyl group.
[0058] for example, [ka] It is.
[0059] Alternatively, a hydroxyl-terminated wax suitable for forming a (meth)acrylate-functionalized wax in accordance with the present invention may have the formula: [ka] In the formula, o is in the range of about 15 to about 35.
[0060] Suitably, o is in the range of about 25 to about 30.
[0061] Alternatively, a hydroxyl-terminated wax suitable for forming a (meth)acrylate-functionalized wax in accordance with the present invention may have the formula: [ka] In the formula, p is 10 to 30.
[0062] Suitably, p is in the range of from about 12 to about 18.
[0063] Suitable commercial examples of such waxes include UNILIN 350, UNILIN 425 and UNILIN 550, which have Mn approximately equal to 375, 460, and 550 g / mol, respectively. UNILIN 700 can also be used. All of these waxes are commercially available from Baker-Petrolite. Guerbet alcohols, characterized as 2,2-dialkyl-1-ethanols, are also suitable choices. Suitable examples of Guerbet alcohols include those containing 16 to 36 carbons, many of which are commercially available from Jarchem Industries Inc., Newark, NJ. Another suitable choice is ISOFOL® 28, which is 2-dodecylhexadecanol, commercially available from Sasol North America Inc., Westlake, LA. PRIPOL 2033 Dimerdiol (C36 dimerdiol mixture), available from Croda, Inc., New Castle, DE, is another suitable commercial choice. More suitable choices are ETERNACOLL UH-50, ETERNACOLL UH-100, and ETERNACOLL UH-200. ETERNACOLL UC-100 can also be used.
[0064] (Meth)acrylate functionalized waxes can be synthesized by reaction of a hydroxyl functional wax with a compound that provides a (meth)acrylate functionality. Hydroxyl functional waxes can be formed from carboxyl functional waxes, which are reduced to the corresponding hydroxyl functional waxes.
[0065] Curable compositions, particularly well suited for adhesive and sealant applications, such as those anaerobically curable, can be prepared using (meth)acrylate-functionalized waxes.
[0066] A method of making a (meth)acrylate-functionalized wax is also provided, in which a wax having one or more hydroxyl groups can be reacted with a compound containing at least one isocyanate group and at least one (meth)acrylate group.
[0067] Anaerobic curable adhesive and sealant compositions are generally based on a (meth)acrylate component along with an anaerobic cure-inducing composition. In the present invention, an additional component is added that is solid at room temperature and reactive with the (meth)acrylate component. Because this additional component is solid, it produces a curable composition that is at least highly viscous, if not completely solid, at room temperature. And because the additional solid component is reactive with the (meth)acrylate component, unlike known highly viscous or completely solid curable compositions in which the increase in viscosity was usually caused by a component that does not react with the (meth)acrylate component, the curable composition of the present invention can reach performance levels not known before.
[0068] Thus, the anaerobically curable composition includes a (meth)acrylate component, an anaerobic cure-inducing composition and a (meth)acrylate-functionalized wax.
[0069] (Meth)acrylate functionalized waxes can be formed from a wax having one or more hydroxyl groups reacted with a compound containing at least one isocyanate group and at least one (meth)acrylate group. Under appropriate reaction conditions, the hydroxyl groups on the wax react with the isocyanate groups to form urethane linkages that leave (meth)acrylate groups available to participate in curing reactions with other components of the curable composition.
[0070] The (meth)acrylate-functionalized waxes of the present invention are non-flowable or in a solid state at room temperature (25° C.).
[0071] For example, the formula [ka] A (meth)acrylate functionalized wax compound having the formula: may be formed by the following reaction sequence: [ka]
[0072] Those skilled in the art will appreciate that alternative synthetic routes may be used to synthesize the (meth)acrylate-functionalized waxes of the present invention.
[0073] (Meth)acrylate monomers suitable for use as the (meth)acrylate component of the present invention include H2C=CGCO2R 8 where G may be hydrogen, halogen, or an alkyl group having 1 to about 4 carbon atoms; R 8 may be selected from alkyl, cycloalkyl, alkenyl, cycloalkenyl, alkaryl, alkaryl or aryl groups having 1 to about 16 carbon atoms, which may optionally be substituted or blocked with silane, silicon, oxygen, halogen, carbonyl, hydroxyl, ester, carboxylic acid, urea, urethane, carbonate, amine, amide, sulfur, sulfonate, sulfone, etc.).
[0074] Additional (meth)acrylate monomers suitable for use in the present invention include, for example, polyethylene glycol di(meth)acrylate, tetrahydrofuran (meth)acrylate and di(meth)acrylate, hydroxypropyl (meth)acrylate ("HPMA"), hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate ("TMPTMA"), diethylene glycol dimethacrylate, triethylene glycol dimethacrylate ("TRIEGMA"), tetraethylene glycol di(meth)acrylate, dipropylene diglycol (meth)acrylate, di(pentamethylene glycol) di(meth)acrylate, dipropylene glycol di(meth)acrylate, di(pentamethylene glycol) ... and polyfunctional (meth)acrylate monomers such as di- or trifunctional (meth)acrylates such as bisphenol-A-mono- and di(meth)acrylates, tetraethylene diglycol di(meth)acrylate, diglycerol tetra(meth)acrylate, tetramethylene di(meth)acrylate, ethylene di(meth)acrylate, neopentyl glycol di(meth)acrylate, and ethoxylated bisphenol-A (meth)acrylate ("EBIPMA"), and bisphenol-F-mono- and di(meth)acrylates, such as ethoxylated bisphenol-A (meth)acrylate.
[0075] For example, the anaerobic curable component may contain (as the anaerobic curable monomer) the following bisphenol A dimethacrylate, which has a melting point of approximately 72-74°C.
[0076] [ka]
[0077] Still other (meth)acrylate monomers that can be used herein include silicone (meth)acrylate moieties ("SiMA") as taught and claimed by U.S. Pat. No. 5,605,999 (Chu), the disclosure of which is incorporated herein by reference.
[0078] Other suitable monomers include polyacrylate esters represented by the formula:
[0079] [ka] During the ceremony, R 4 is a group selected from hydrogen, halogen, or alkyl having 1 to about 4 carbon atoms; q is an integer equal to at least 1, preferably 1 to about 4; and X is an organic group containing at least 2 carbon atoms and having a total binding capacity of q+1. With respect to the upper limit of the number of carbon atoms in X, there are monomers that can function with essentially any value. However, in practice, a common upper limit is about 50 carbon atoms, preferably 30, and most preferably about 20.
[0080] For example, X can be an organic group of the formula:
[0081] [ka] During the ceremony, Y 1 and Y 2 Each of is an organic group such as a hydrocarbon group containing at least 2 carbon atoms, desirably from 2 to about 10 carbon atoms, and Z is an organic group, preferably a hydrocarbon group containing at least 1 carbon atom, preferably from 2 to about 10 carbon atoms.
[0082] Another class of useful monomers are the reaction products of di- or tri-alkylolamines (e.g., ethanolamine or propanolamine) with acrylic acid, as disclosed in French Patent No. 1,581,361. Examples of useful acrylic ester oligomers include those having the general formula:
[0083] [ka] In the formula, R 5is hydrogen, a lower alkyl having 1 to about 4 carbon atoms, a hydroxyalkyl having 1 to about 4 carbon atoms, or
[0084] [ka] is a group selected from R 4 is a group selected from hydrogen, halogen, or lower alkyl having 1 to about 4 carbon atoms; R 6 is hydrogen, hydroxyl or
[0085] [ka] and m is an integer at least equal to 1, for example, 1 to about 15 or more, desirably 1 to about 8; n is an integer at least equal to 1, for example, 1 to about 40 or more, desirably about 2 to about 10; and p is 0 or 1.
[0086] Representative examples of acrylic ester oligomers corresponding to the above general formula include di-, tri-, and tetraethylene glycol dimethacrylate; di(pentamethylene glycol) dimethacrylate; tetraethylene glycol diacrylate; tetraethylene glycol di(chloroacrylate); diglycerol diacrylate; diglycerol tetramethacrylate; butylene glycol dimethacrylate; neopentyl glycol diacrylate; and trimethylolpropane triacrylate.
[0087] Di- and other polyacrylate esters, especially those described in the previous paragraph, are desirable, but monofunctional acrylate esters (esters containing one acrylate group) can also be used. When working with monofunctional acrylate esters, it is highly preferred to use esters with relatively polar alcohol moieties. Such materials are less volatile than low molecular weight alkyl esters, and more importantly, produce more desirable curing properties and more durable sealants or adhesives, since the polar groups tend to provide intermolecular attractions during and after curing. Most preferably, the polar groups are selected from labile hydrogen, heterocyclic, hydroxy, amino, cyano, and halo polar groups. Typical examples of compounds within this category are cyclohexyl methacrylate, tetrahydrofurfuryl methacrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, t-butylaminoethyl methacrylate, cyanoethyl acrylate, and chloroethyl methacrylate.
[0088] Another useful class of monomers is prepared by the reaction of monofunctionally substituted alkyl or aryl acrylate esters containing active hydrogen atoms on the functional substituent. The monofunctional acrylate terminated materials are reacted with organic polyisocyanates in the appropriate ratios to convert all the isocyanate groups to urethane or ureido groups. The monofunctional alkyl and aryl acrylate esters are preferably acrylates and methacrylates that contain hydroxy or amino functional groups in the non-acrylate portion. Suitable acrylate esters for use have the formula:
[0089] [ka] During the ceremony, X is -O- and
[0090] [ka] is selected from R9 is selected from hydrogen or lower alkyl having 1 to 7 carbon atoms; R 7 is selected from hydrogen, halogen (e.g., chlorine) or alkyl (e.g., methyl and ethyl groups); R 8 is a divalent organic radical selected from lower alkylene having 1 to 8 carbon atoms, phenylene, and naphthylene.
[0091] These groups, upon appropriate reaction with a polyisocyanate, produce monomers of the general formula:
[0092] [ka] where n is an integer from 2 to about 6; B is a polyvalent organic group selected from alkyl, alkenyl, cycloalkyl, cycloalkenyl, aryl, alkaryl, and heterocyclic groups, both substituted and unsubstituted; R 7 , R 8 and X has the above meaning.
[0093] Depending on the characteristics of B, these (meth)acrylate esters having urea or urethane bonds may have a molecular weight that places them in the oligomeric class (such as from about 1,000 g / mol to about 5,000 g / mol) or polymeric class (e.g., greater than about 5,000 g / mol).
[0094] Desirably, the anaerobic curable component is selected from at least one of epoxy (meth)acrylates, urethane (meth)acrylates, urethane di(meth)acrylates, alkyl (meth)acrylates, stearyl (meth)acrylates, isocyanurate (meth)acrylates, bisphenol-A-(meth)acrylates, ethoxylated bisphenol-A-(meth)acrylates, bisphenol-F-(meth)acrylates, ethoxylated bisphenol-F-(meth)acrylates, bisphenol-A di(meth)acrylates, ethoxylated bisphenol-A-di(meth)acrylates, bisphenol-F-di(meth)acrylates, ethoxylated bisphenol-F-di(meth)acrylates, and the like.
[0095] For example, the anaerobic curable component may be a diisocyanate capped with hydroxyethyl methacrylate (as the anaerobic curable monomer), such as: HEMA-IPDI-HEMA has a melting point of about 72-74°C.
[0096] [ka]
[0097] : or HEMA-HMDI-HEMA having a melting point of about 75 to 85 ° C.
[0098] [ka]
[0099] or HEMA-1,3-CHDI-HEMA having a melting point of about 75 to 85 ° C. ("RRT600" in the following examples);
[0100] [ka]
[0101] or glycerol dimethacrylate-6HXDI-glycerol dimethacrylate ("4RRT600" in the following examples) having a melting point in the range of about 75 to about 85 ° C.
[0102] [ka] etc.
[0103] The ratio in which the reactants can be combined can vary somewhat, however, it is generally preferred to use chemically equivalent amounts of the reactants up to a slight excess.
[0104] Desirably, at least a portion of the (meth)acrylate component should be in a solid state at room temperature, and particularly desirably, should be capable of changing state from solid to liquid under elevated temperature conditions. For example, 2-methacryloxyethylphenylurethane, which is solid at room temperature, is a particularly desirable (meth)acrylate for use as at least a portion of the (meth)acrylate component, and is indeed used in the exemplary compositions formulated in the Examples.
[0105] Of course, combinations of these (meth)acrylate monomers can also be used.
[0106] The (meth)acrylate component can be included in about 10 to about 95 wt% of the composition, for example, about 20 to about 90 wt%, or about 30 to about 85 wt%, for example, about 35 to about 80 wt%, or about 40 to about 75 wt%, for example, about 60 to about 75 wt%, based on the total weight of the composition.
[0107] Additional components have been included in conventional anaerobic adhesives in the past to alter the physical properties of either the formulation or its reaction products. For example, one or more maleimide components, co-reactants that impart heat resistance, diluent components reactive at high temperature conditions, mono- or polyhydroxyalkanes, polymeric plasticizers, and chelating agents (see U.S. Pat. No. 6,391,993, incorporated herein) may be included to modify the physical properties and / or cure profile of the formulation, and / or the strength or heat resistance of the cured adhesive.
[0108] If used, the maleimide, co-reactant, reactive diluent, plasticizer, and / or mono- or polyhydroxyalkane may be present in an amount in the range of about 1% by weight to about 30% by weight, based on the total weight of the composition.
[0109] The anaerobic cure-inducing composition includes one or more of a free radical initiator, a free radical accelerator, and a free radical stabilizer. Metal catalysts may also be used.
[0110] Typically, many well-known initiators of free radical polymerization are incorporated into the anaerobic curable compositions, including, but not limited to, hydroperoxides such as cumene hydroperoxide ("CHP"), paramenthane hydroperoxide, t-butyl hydroperoxide ("TBH"), t-butyl perbenzoate, and the like. Other peroxides include benzoyl peroxide, dibenzoyl peroxide, 1,3-bis(t-butylperoxyisopropyl)benzene, diacetyl peroxide, butyl 4,4-bis(t-butylperoxy)valerate, p-chlorobenzoyl peroxide, t-butylcumyl peroxide, t-butyl perbenzoate, di-t-butyl peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-di-t-butylperoxyhexane, 2,5-dimethyl-2,5-di-t-butyl-peroxyhex-3-yne, 4-methyl-2,2-di-t-butylperoxypentane, t-amyl hydroperoxide, 1,2,3,4-tetramethylbutyl hydroperoxide and combinations thereof.
[0111] Encapsulated peroxides can also be used. For example, encapsulated benzoyl peroxide can be used. Encapsulated benzoyl peroxide with a particle size of 200 μm, available from Japan Capsular Products, is one particularly useful material. Others with particle sizes in the 100 μm range are also desirable. Besides Japan Capsular Products, commercial sources of encapsulated benzoyl peroxide include Lipo Technologies Inc. and RT Dodge.
[0112] Such peroxides are typically used in the present invention in the range of from about 0.1 to about 10 weight percent, and preferably from about 1 to about 5 weight percent, based on the total weight of the composition.
[0113] As previously mentioned, conventional accelerators for free radical polymerization are typically of the hydrazine type (e.g., APH), as disclosed in U.S. Patents 4,287,350 (Rich) and 4,321,349 (Rich). Maleic acid is usually added to APH-containing anaerobic cure-inducing compositions.
[0114] Free radical polymerization co-promoters may also be used in the compositions of the present invention, including, but not limited to, organic amides and imides such as benzoic acid sulfimide (also known as saccharin) (see U.S. Pat. No. 4,324,349).
[0115] The accelerator (or co-accelerator) can be used in an amount of from about 0.1 to about 5% by weight, for example, from about 1 to about 2% by weight, based on the total weight of the composition.
[0116] Stabilizers and inhibitors, such as phenolic containing hydroquinones and quinones, may also be used to control and prevent premature peroxide decomposition and polymerization of the compositions of the present invention.
[0117] Chelating agents, such as the tetrasodium salt of ethylenediaminetetraacetic acid ("EDTA"), can be used to trap trace amounts of metal contaminants. If used, the chelating agent may typically be present in the composition in an amount of about 0.001% to about 0.1% by weight, based on the total weight of the composition.
[0118] Other additives such as plasticizers, fillers, reinforcing agents (such as elastomers and rubbers) and other well known additives may be incorporated therein as would be deemed desirable by one skilled in the art.
[0119] The present invention also provides methods of preparing and using the anaerobic adhesive and sealant compositions of the present invention, as well as the reaction products of the compositions.
[0120] The compositions of the present invention can be prepared using conventional methods well known to those skilled in the art.For example, the components of the anaerobic adhesive and sealant compositions of the present invention can be mixed together in any convenient order consistent with the role and function that the components perform in the composition.Conventional mixing techniques using known equipment can be used.
[0121] The composition of the present invention can be applied to various substrates to achieve the desired benefits and advantages described herein. For example, suitable substrates can be constructed from steel, brass, copper, aluminum, zinc, and other metals and alloys, ceramics, and thermosetting resins. A suitable primer for the anaerobic curing composition can be applied to the surface of the selected substrate to enhance the curing rate. Alternatively, the anaerobic curing accelerator of the present invention can be applied to the surface of the substrate as a primer. For example, see U.S. Patent No. 5,811,473 (Ramos).
[0122] The present invention also provides a process for preparing a reaction product from the anaerobic curable composition of the present invention, the steps of which include applying the composition to a desired substrate surface and exposing the composition to an anaerobic environment for a period of time sufficient to cure the composition.
[0123] Advantageously, the compounds of the present invention are softer and have a lower melting range than prior art urethane-functionalized (meth)acrylates. Furthermore, the compositions of the present invention have improved lubricity compared to prior art compositions containing urethane-functionalized (meth)acrylates. This is particularly advantageous in thread locking applications.
[0124] In light of the above discussion, it will be apparent that the following provides a wide range of practical opportunities which are for illustrative purposes only. EXAMPLES
[0125] <Synthesis of (meth)acrylate-containing wax> Example 1: To a 500 mL reaction kettle equipped with an overhead stirrer and nitrogen inlet / outlet was added 150.16 g (0.367 equivalents of OH) of a hydroxyl functionalized wax (commercially available as Unilin 350). The kettle was heated to a temperature of 85° C. to melt the wax. Once melted, 0.04 g of dibutyltin dilaurate was added with mixing. Next, 57.06 g (0.367 equivalents of NCO) of 2-isocyanoethyl methacrylate was added with mixing under nitrogen for 3 hours (see also FIG. 1). The NCO consumption was monitored by FT-IR (2200 cm -1 ) and after 3 hours the NCO was completely reacted to produce a 100% methacrylated functionalized wax.
[0126] [ka]
[0127] <Synthesis of extended (meth)acrylate-containing wax> Example 2: To a 500 ml reaction kettle equipped with an overhead stirrer and nitrogen inlet / outlet was added 114.80 g (0.281 equivalents of OH) of hydroxyl functionalized wax (commercially available as Unilin 350). The kettle was heated to a temperature of 85° C. to melt the wax. Once melted, 0.03 g of dibutyltin dilaurate was added with mixing. Next, 11.84 g (0.141 equivalents of NCO) of hexane diisocyanate was added with mixing under nitrogen for 1 hour. Next, 20.74 g (0.134 equivalents of NCO) of 2-isocyanoethyl methacrylate was added with mixing under nitrogen for 3 hours. The NCO consumption was measured by FT-IR (2200 cm -1 ) and after 3 hours, the NCO was completely reacted to produce the extended methacrylate functionalized wax.
[0128] Methacrylated and IPDI extended polycarbonate diol waxes with 1,4-butadiene diol hard segments Example 3: To a 500 mL reaction kettle equipped with an overhead stirrer and nitrogen inlet / outlet, 207.58 g (0.138 equivalents of OH) of polycarbonate diol wax (commercially available as Eternacoll UH-300) and 0.02 g of phosphoric acid were added. The kettle was slowly heated to a temperature of 75° C. with mixing to melt the polycarbonate diol. Once melted, 0.21 g of dibutyltin dilaurate and 0.69 g (0.015 equivalents of OH) of 1,4-butanediol were added with mixing. Next, 3.39 g (0.030 equivalents of NCO) of isophorone diisocyanate were weighed out with mixing under nitrogen and allowed to react for 1 hour. Next, 18.92 g (0.122 equivalents of NCO) of 2-isocyanoethyl methacrylate were added with mixing under nitrogen for 3 hours. The NCO consumption was measured by FT-IR (2200 cm -1 ) and after 3 hours, the NCO was completely reacted to produce the methacrylated extended polycarbonate diol wax.
[0129] Methacrylated and HDI extended polycarbonate diol waxes with 1,4-butadiene diol hard segments Example 4: To a 500 mL reaction kettle equipped with an overhead stirrer and nitrogen inlet / outlet, 251.67 g (0.163 equivalents of OH) of polycarbonate diol wax (commercially available as Eternacoll UH-300) and 0.03 g of phosphoric acid were added. The kettle was slowly heated to a temperature of 75° C. with mixing to melt the polycarbonate diol. Once melted, 0.26 g of dibutyltin dilaurate and 1.87 g (0.042 equivalents of OH) of 1,4-butanediol were added with mixing. Next, 5.25 g (0.062 equivalents of NCO) of hexamethylene diisocyanate was weighed out with mixing under nitrogen and allowed to react for 1 hour. Next, 22.58 g (0.146 equivalents of NCO) of 2-isocyanoethyl methacrylate was added with mixing under nitrogen for 3 hours. The NCO consumption was monitored by FT-IR (2200 cm -1 ) and after 3 hours, the NCO was completely reacted to produce the methacrylated extended polycarbonate diol wax.
[0130] Methacrylated and HDI extended polycarbonate diol waxes with 1,4-butadiene diol hard segments Example 5: To a 500 mL reaction kettle equipped with an overhead stirrer and nitrogen inlet / outlet, 201.30 g (0.387 equivalents of OH) of polycarbonate diol wax (commercially available as Eternacoll UH-100) and 0.02 g of phosphoric acid were added. The kettle was slowly heated to a temperature of 75° C. with mixing to melt the polycarbonate diol. Once melted, 0.22 g of dibutyltin dilaurate and 4.36 g (0.097 equivalents of OH) of 1,4-butanediol were added with mixing. Next, 12.22 g (0.145 equivalents of NCO) of hexamethylene diisocyanate was weighed out with mixing under nitrogen and allowed to react for 1 hour. Next, 52.60 g (0.339 equivalents of NCO) of 2-isocyanoethyl methacrylate was added with mixing under nitrogen for 3 hours. The consumption of NCO was measured by FT-IR (2200 cm -1 ) and after 3 hours, the NCO was completely reacted to produce the methacrylated extended polycarbonate diol wax.
[0131] Methacrylated and IPDI extended polyester diol waxes with 1,4-butadiene diol hard segments Example 6: 192.72 g (0.137 equivalents of OH) of polyester diol wax (commercially available as Priplast 3172-SO-(GD)) was added to a 500 mL reaction kettle equipped with an overhead stirrer and nitrogen inlet / outlet. The kettle was slowly heated to a temperature of 75° C. with mixing to melt the polyester diol. Once melted, 0.22 g of dibutyltin dilaurate and 1.54 g (0.034 equivalents of OH) of 1,4-butanediol were added with mixing. Next, 28.78 g (0.342 equivalents of NCO) of isophorone diisocyanate was weighed out with mixing under nitrogen and allowed to react for 1 hour. Next, 22.26 g (0.171 equivalents of OH) of 2-hydroxyethyl methacrylate was added with mixing under nitrogen for 3 hours. The NCO consumption was measured by FT-IR (2200 cm -1 ) and after 3 hours, the NCO was completely reacted to produce the extended methacrylated polyester diol wax.
[0132] <Preparation of anaerobic curable composition> Example 7: The following components set forth in the table below were used to make an anaerobic curable composition for evaluation.
[0133] [Table 1]
[0134] The formulations were applied to black oxide and mild steel substrates, as well as zinc phosphate coated steel substrates, and cured as described for periods ranging from 24 hours to 168 hours. After these periods, the breaking torque performance was measured and recorded. The measurements can be seen with reference to Figure 2 and as shown in the table below.
[0135] [Table 2]
[0136] Example 8: An anaerobic curable composition for evaluation was made using the following components set forth in the table below.
[0137] [Table 3]
[0138] The formulations were applied to black oxide and mild steel substrates and cured as described for periods ranging from 24 hours to 168 hours. After these periods, the breaking torque performance was measured and recorded.
[0139] [Table 4]
[0140] The average advantage of the composition of Example 8 was 7.1 Nm.
[0141] The breaking torque performance and prevailing strength were measured according to ASTM D5649 "Torque Strength of Adhesives Used in Threaded Fasteners". The nuts and bolts were degreased prior to assembling with the formulations. The breaking strength is the initial torque required to break the bond as measured at the initial movement between the nut and bolt when the assembly is loosened.
[0142] Suitably, the compositions of the present invention have a minimum breaking torque strength against black oxide / mild steel or zinc phosphate as determined according to ASTM D5649 of at least 15 N.m after 72 hours.
[0143] <Differential Scanning Calorimetry (DSC)> Differential scanning calorimetry (DSC) can show the physical properties of functionalized resins by determining the heat flux response to changes in thermal conditions. Samples were analyzed using a Perkin Elmer DSC6000 according to ISO11357-1:2016. The sample to be analyzed was placed in an aluminum pan in an amount of 10-15 mg and placed in a sample holder in a furnace. The thermogram obtained from the analysis shows the endothermic response as an increase in mW and the exothermic response as a decrease in mW. The sample was heated from -30°C to 100°C at a rate of 10°C per minute and then cooled to -20°C at a rate of 10°C / min. The sample in Figure 3 shows a thermogram of the urethane methacrylate functionalized wax resin from Example 3. Figure 4 shows a thermogram of the urethane methacrylate functionalized semi-crystalline polyester resin. As shown in Figure 4, the resin shows an endothermic melting with an onset at 64.6°C and an exothermic recrystallization with a peak at 48.45°C. In contrast, the thermogram of the product of Example 3 in Figure 3 shows an onset of a melting peak at 29.20°C with no corresponding recrystallization peak above 0°C. This indicates that the product of Example 3 has a lower melting temperature than the resin of Figure 3. Furthermore, the product of Example 3 is a softer, amorphous material at room temperature since no recrystallization occurs. Advantageously, such a product can be used to produce a solid threadlock composition with improved lubricity.
[0144] When used in reference to the present invention, the words "comprises" and "having" are used to specify the presence of stated features, integers, steps or components, but do not exclude the presence or addition of one or more other features, integers, steps, components or groups thereof.
[0145] It is appreciated that certain features of the invention that are, for clarity, described in the context of separate embodiments, may also be provided in combination in a single embodiment. Conversely, various features of the invention that are, for brevity, described in the context of a single embodiment, may also be provided separately or in any suitable subcombination.
Claims
1. (Meth)acrylate component and additionally, from 10% to 60% by weight, based on the total weight of the composition. formula 【Chemistry 1】 (In the formula, n is 0 to 3, t is 1 to 4, and Z is H or Me; R is 1 or more C 1 ~C 6 Alkyl, C 1 ~C 6 C optionally substituted with alkoxy, hydroxyl, acrylate, methacrylate, oxo 2 ~C 12 is an aliphatic group, 2 ~C 12 The aliphatic group is optionally substituted with one or more heteroatoms selected from O, N or S; R 1 is 1 or more C 1 ~C 6 Alkyl group, C 1 ~C 6 C optionally substituted with alkoxy, hydroxyl, oxo, carbonate, or one or more heteroatoms selected from O, N, or S; 10 ~C 120 is an aliphatic group, a residue derived from a wax having two or more hydroxyl groups; R 2 is 1 or more C 1 ~C 6 Alkyl, C 1 ~C 6 C optionally substituted with alkoxy, hydroxyl, and one or more heteroatoms selected from O, N, or S; 2 ~C 20 Aliphatic group or C 5 ~C 20 2. A threadlocker composition comprising a (meth)acrylate functionalized wax represented by the formula:
2. R is C 2 ~C 12 10. The threadlock composition of claim 1, wherein the threadlock composition is an alkylene.
3. 3. The threadlock composition of claim 2, wherein R is ethylene, propylene, butylene, pentylene, hexylene, or an isomer thereof.
4. R 1 But, C 18 ~C 40 2. The thread lock composition of claim 1, wherein
5. 2. The thread lock composition of claim 1, wherein n is 0, 1 or 2.
6. 2. The thread lock composition of claim 1, wherein t is 1, 2, or 3.
7. R 1 but, 【Chemistry 2】 (In the formula, R 3 is C 1 ~C 12 It is an alkyl group.
2. The thread lock composition of claim 1, wherein
8. R 1 but, 【Chemistry 3】 8. The thread lock composition of claim 7, wherein
9. (Meth)acrylate component and additionally, from 10% to 60% by weight, based on the total weight of the composition. formula 【Chemistry 4】 (In the formula, n is 0 to 3, t is 1 to 4, and Z is H or Me; R is 1 or more C 1 ~C 6 Alkyl, C 1 ~C 6 C optionally substituted with alkoxy, hydroxyl, acrylate, methacrylate, oxo 2 ~C 12 is an aliphatic group, 2 ~C 12 The aliphatic group is optionally substituted with one or more heteroatoms selected from O, N or S; R 1 teeth, 【Chemistry 5】 (In the formula, o is 15 to 30.) or 【Chemistry 6】 (In the formula, p is 10 to 30.) It is expressed as R 2 is 1 or more C 1 ~C 6 Alkyl, C 1 ~C 6 C optionally substituted with alkoxy, hydroxyl, and one or more heteroatoms selected from O, N, or S; 2 ~C 20 Aliphatic group or C 5 ~C 20 2. A threadlocker composition comprising a (meth)acrylate functionalized wax represented by the formula:
10. R 2 But, C 2 ~C 12 10. The threadlock composition of claim 1 or 9, wherein the alkylene is an alkylene.
11. R 2 11. The thread lock composition of claim 10, wherein is selected from the group consisting of ethylene, propylene, butylene, pentylene, hexylene, cyclopentylene, cyclohexylene, heptylene, octylene and isomers thereof.
12. R 2 but, 【Chemistry 7】 (wherein x is 1 to 4, and each R 4 is C 1 ~C 6 Alkyl or C 1 ~C 6 alkoxy.) 10. The thread lock composition of claim 1 or 9,
13. R 2 but, 【Chemistry 8】 10. The thread lock composition of claim 1 or 9,
14. R 2 but, 【Chemistry 9】 10. The thread lock composition of claim 1 or 9, 15. The (meth)acrylate functionalized wax comprising: 【Chemistry 10】 【Chemistry 11】 【Chemistry 12】 2. The thread lock composition of claim 1 selected from: (c) the (meth)acrylate-functionalized wax comprising: 【Chemistry 13】 2. The thread lock composition of claim 1, wherein 17. The thread lock composition of claim 1 or 9, comprising one or more of a free radical initiator, a free radical promoter, and a free radical stabilizer.
18. The free radical initiator is selected from the group consisting of cumene hydroperoxide, paramenthane hydroperoxide, t-butyl hydroperoxide, t-butyl perbenzoate, benzoyl peroxide, dibenzoyl peroxide, 1,3-bis(t-butylperoxyisopropyl)benzene, diacetyl peroxide, butyl 4,4-bis(t-butylperoxy)valerate, p-chlorobenzoyl peroxide, t-butylcumyl peroxide, lauryl peroxide, urea-hydrogen peroxide, n-vinylpyrrolidone-hydrogen peroxide, bis(t-butylcyclohexyl peroxide), and the like.
18. The thread lock composition of claim 17 comprising a peroxide or hydroperoxide selected from the group consisting of didicarbonate, t-butyl perbenzoate, di-t-butyl peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-di-t-butylperoxyhexane, 2,5-dimethyl-2,5-di-t-butyl-peroxyhex-3-yne, 4-methyl-2,2-di-t-butylperoxypentane, t-amyl hydroperoxide, 1,2,3,4-tetramethylbutyl hydroperoxide, and combinations thereof.
19. The thread lock composition of claim 1 or 9, wherein the (meth)acrylate functionalized wax is present in an amount of 25% to 50% by weight, based on the total weight of the composition.
Citation Information
Patent Citations
Photocuring adhesive composition and optical member using same
JP2000038546A
Polyurethane (METH) acrylate, and composition and cured product thereof
JP2018131521A
Anaerobic hardening components
JP2019500438A
(Meth)acrylate-functionalized waxes and curable compositions made therewith
JP2022521449A
Anaerobically curable compositions
US20180237661A1